Molecular detection of Coxiella burnetii in aborted bovine fetuses in Brazil - Mioni, Mateus de Souza Ribeiro [UNESP]; Henker, Luan Cleber; Teixeira, Wanderson Sirley Reis [UNESP]; Lorenzett, Marina Paula; Labruna, Marcelo Bahia; Pavarini, Saulo Petinatti; Driemeier, David; Rousset, Élodie; Sidi-Boumedine, Karim; Thiéry, Richard; Megid, Jane [UNESP] (Elsevier, 2022)
In the past decade, cases of Q fever have been reported in Brazil. Although the previous report of Coxiella burnetii in humans and animals, the knowledge about the occurrence of this pathogen in livestock in Brazil is scarce. This study aimed to search C. burnetii and possible coinfections in tissues of aborted bovine fetuses from Brazil. Tissue samples from seventy-six aborted bovine fetuses sent to the laboratory of molecular diagnosis of infectious diseases from 2013 to 2019 were evaluated by real-time PCR for C. burnetii. Overall, 9.2% (7/76) of the samples were positive for C. burnetii. Moreover, the molecular diagnostic history of our lab revealed the coinfection with Neospora spp. in three fetuses and the presence of histopathological features suggestive with fetal neosporosis in another one. The previous report of C. burnetii in humans and animals in the country, with the detection of C. burnetii from tissues of aborted bovine fetuses reported here, reinforces the neglected state of the disease in Brazil and raises the question of the role of the pathogen in reproductive disorders in national livestock.
Keywords: Abortion; Cattle; Public health; Q fever